Literature Review: The Effect of Spiritual Emotional Freedom Technique Therapy on Patients with Depression - Sucipto Sucipto; Heny Kristanto; Wijayanti Chintya Dhevansa (GLOBAL HEALTH SCIENCE GROUP, 2023)
Depression is a disorder of a person's feelings, emotions and behavior negatively which can make a person feel lost, empty and have no zest for life. To treat depression, you can use Spiritual Emotional Freedom Technique (SEFT) therapy which aims to change feelings, thoughts to become calmer and relaxed. and willingly accept trials. The purpose of this study was to analyze a journal entitled the effect of SEFT therapy on patients with depression. The research design used a literature review with a data collection strategy using inclusion-exclusion in the PICOS format. The search method in this study used the Google Scholar and Semantic Scholar databases by entering the words